Application of aqueous saline process to extract silkworm pupae oil (Bombyx mori): process optimization and composition analysis - Tangsanthatkun, Janjira; Peanparkdee, Methavee; Katekhong, Wattinee; Harnsilawat, Thepkunya; Tan, Chin Ping; Klinkesorn, Utai (MDPI, 2022)
Silkworm pupae, a waste product from the silk production industry, can be an alternative source of edible oil, thus reducing the industry’s waste. In the present work, frozen silkworm pupae were used as raw material to extract oil via an aqueous saline process. The Box–Behnken design (BBD) and response surface methodology (RSM) were used to optimize the extraction process. The extraction conditions with the highest oil yield and a low peroxide value were obtained when using a saline solution concentration of 1.7% w/v, a ratio of aqueous liquid to silkworm pupae of 3.3 mL/g, and a 119 min stirring time at the stirring speed of 100 rpm. Under these conditions, silkworm oil with a yield of 3.32%, peroxide values of approximately 1.55 mM, and an acid value of 0.67 mg KOH/g oil was obtained. The extracted oil contained omega-3 acids (α-linolenic acid), which constituted around 25% of the total fatty acids, with approximate cholesterol levels of 109 mg/100 g oil. The amounts of β-carotene and α-tocopherol were approximately 785 and 9434 μg/100 g oil, respectively. Overall, the results demonstrated that oil extracted from silkworm pupae has good quality parameters and thus can be used as a new valuable source of edible lipids.